Staged use of ordinal and linear disability scales: a practical approach to granular assessment of acute stroke outcome - Chaisinanunkul, Napasri; Starkman, Sidney; Gornbein, Jeffrey; Hamilton, Scott; Chatfield, Fiona; Conwit, Robin; Saver, Jeffrey L. (Frontiers in Neurology, 2023)
Background: The modified Rankin Scale (mRS) assessment of global disability is most common primary endpoint in acute stroke trials but lacks granularity (7 broad levels) and is ordinal (scale levels unknown distances apart), constraining study power. Disability scales that are linear and continuous may better discriminate outcomes, but computerized administration in stroke patients is challenging. We therefore undertook to develop staged use of an ordinal followed by a linear scale practical to use in multicenter trials. Methods: Consecutive patients undergoing 3 month final visits in the NIH FAST-MAG phase 3 trial were assessed with the mRS followed by an mRS-mapped version of the Academic Medical Center Linear Disability Scale (ALDS), a linear disability scale derived using item response theory. Results: Among 55 patients, age was 71.2 (SD±14.2), 67% were male, and entry NIHSS was 10.7 (SD±9.5). At 90 days, the median mRS was 3 (IQR 1 - 4) and median ALDS score 78.8 (IQR 3.3-100). ALDS scores correlated strongly with 90d outcome measures, including Barthel Index (r=0.92), NIHSS (r=0.87), and mRS (r = 0.94). ALDS scores also correlated modestly with entry NIHSS (r = 0.38). At 90 days, the ALDS showed greater scale granularity than the mRS, with fewer patients with identical values, 1.9 (SD±3.2) vs 8.0 (SD±3.6), p < 0.001. When treatment effect magnitudes were small to moderate, projected trial sample size requirements were 2-12 fold lower when the ALDS rather than the mRS was used as the primary trial endpoint.